Isolation of a bacteriophage targeting Pseudomonas aeruginosa and exhibits a promising in vivo efficacy - Aliaa Abdelghafar; Amira El-Ganiny; Ghada Shaker; Momen Askoura (AMB Express, 2023)
Abstract Pseudomonas aeruginosa is an important pathogen that causes serious infections. Bacterial biofilms are highly resistant and render bacterial treatment very difficult, therefore necessitates alternative antibacterial strategies. Phage therapy has been recently regarded as a potential therapeutic option for treatment of bacterial infections. In the current study, a novel podovirus vB_PaeP_PS28 has been isolated from sewage with higher lytic activity against P. aeruginosa. Isolated phage exhibits a short latent period, large burst size and higher stability over a wide range of temperatures and pH. The genome of vB_PaeP_PS28 consists of 72,283 bp circular double-stranded DNA, with G + C content of 54.75%. The phage genome contains 94 open reading frames (ORFs); 32 for known functional proteins and 62 for hypothetical proteins and no tRNA genes. The phage vB_PaeP_PS28 effectively inhibited the growth of P. aeruginosa planktonic cells and displayed a higher biofilm degrading capability. Moreover, therapeutic efficacy of isolated phage was evaluated in vivo using mice infection model. Interestingly, survival of mice infected with P. aeruginosa was significantly enhanced upon treatment with vB_PaeP_PS28. Furthermore, the bacterial load in liver and kidney isolated from mice infected with P. aeruginosa and treated with phage markedly decreased as compared with phage-untreated P. aeruginosa-infected mice. These findings support the efficacy of isolated phage vB_PaeP_PS28 in reducing P. aeruginosa colonization and pathogenesis in host. Importantly, the isolated phage vB_PaeP_PS28 could be applied alone or as combination therapy with other lytic phages as phage cocktail therapy or with antibiotics to limit infections caused by P. aeruginosa.